Hatchability Performance Of Different Varieties Of Turkey - Pandian, C.; Sundaresan, A.; Omprakash , A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted for a period of 12 weeks to analyze the hatchability performance of different varieties of turkeys at the age of 30-42 weeks viz Native Turkey, Nandanam Turkey-I and Nandanam turkey-II . The mean per cent fertility of different varieties of turkeys were differed significantly (P
Keywords: Hatchability performance; Varieties; Turkey